STRATEGI PENGEMBANGAN INDUSTRI MINUMAN SIRUP MANGROVE DI KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI - Sari Diana Yessi; Iyan Yani Rita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the development strategy of the mangrove syrup beverage industry in the West Rangsang District, Meranti Islands Regency. Retrieval of data using the census method, namely the entire population of 2 business units. Analysis of the data used is the SWOT analysis, IFAS and EFAS matrix. Based on the results of matrix analysis relating to the main strengths for the beverage industry, mangrove syrup is the ease of obtaining raw materials. The weight and average ranking of internal factors has a high weight and average ranking. The disadvantage is not selling their own products to the market. This means that respondents consider the most important weakness factor compared to other weaknesses. The main opportunity for the mangrove syrup beverage industry in West Rangsang District, Meranti Islands is to increase promotional activities and product development. While the threat of limited technology is a challenge in production activities. This means that respondents consider the most important factor compared to other safety indicators. Based on the IE Matrix in the S-O strategy column, it is because the meeting between IFAS and EFAS is on (opportunities) and (strengths).Keywords: development strategy, small industry.